Labour market deregulation, 'flexibility' and innovation. - Michie, J; Sheehan, M (Oxford University Press, 2003)
Labour ‘flexibility’ is often portrayed as important to competitive success. Using evidence from an original survey of UK firms, this paper investigates the relationships between firms' use of, on the one hand, various flexible work practices, human resource management techniques, and industrial relations systems and, on the other hand, the innovative activities of those firms. Our results suggest that the sort of ‘low road’ labour flexibility practices encouraged by labour market deregulation—short-term and temporary contracts, a lack of employer commitment to job security, low levels of training, and so on—are negatively correlated with innovation.